Functional Themes from Psychiatric Genome-Wide Screens - Davies, William (Frontiers in Genetics, 2011)
Technological advances and a greater degree of inter-laboratory co-operation mean that genome-wide analyses can now be used to identify genetic variants that are robustly associated with the risk of developing psychiatric and neurological disorders. In contrast to the candidate gene approach, such screens may identify variants within genes which have a hitherto unappreciated role in disorder pathogenesis, and whose brain function is obscure. In this Perspective, I discuss how the behavioral functions of such genes may be investigated using model systems, drawing attention to the potential caveats and limitations with such approaches. The power of focused cross-species studies needs to be effectively exploited to enable useful insights into the molecular pathogenesis of common and disabling disorders, and ultimately to provide better clinical outcomes for patients.